PASAR HETEROTOPIA: TIPOLOGI BARU SEBUAH PASAR - Jasson Jasson; Doddy Yuono (Jurusan Arsitektur dan Perencanaan, 2019)
The market, aside from being the place where economic transactions occur, also has an important role as a social network as well as a medium to showcase the existence of self by various parties. Especially to the millennial generation who now tend to enjoy transaction activities virtually. The high rate of digitalization of current economic activities, along with its network expansion to social media, has redefined shopping activities as one of the (commodity) unique experiences that must be experienced and shared by millennials to strengthen their social quality. Millennials view economic-transaction activities as a way of gaining new experiences that deserve to be shared. On the other hand, reflecting on the same tendency in other aspects, the phenomenon of digitalization has helped strengthen millennial individualistic tendencies, isolating themselves from direct contact in the real world. The change in the economic system to digital direction is also possesing new threat to the sustainability of existing conventional economic practices, especially traditional market systems with a very high level of interaction and social participation among its users. Through this project, researchers are trying to offer a new typological form of traditional markets that support the social closeness between their users, intensified, and maintain the essence of traditional markets as a social center of society. The design of the architectural typology offered by researchers is also expected to provide the widest possible opportunity for its users, especially the millennial generation, to explore their various social roles in current economic activities. AbstrakPasar, selain mejadi tempat terjadinya transaksi ekonomi, juga memiliki peran penting sebagai jaringan sosial sekaligus media unjuk eksistensi diri oleh berbagai pihak. Terutama kepada generasi milenial yang sekarang cenderung menikmati kegiatan transaksi secara virtual. Tingginya laju digitalisasi kegiatan ekonomi saat ini, beserta perluasan jaringannya kepada media sosial, telah meredefinisikan kegiatan belanja sebagai salah satu (komoditas) pengalaman unik yang wajib dialami dan dibagikan para milenial untuk memperkuat kualitas sosial dirinya. Generasi milenial memandang kegiatan transaksi-ekonomi sebagai salah satu cara untuk memperoleh pengalaman baru yang patut dibagikan. Di sisi lain, bercermin kepada tendensi sama di aspek-aspek lain, fenomena digitalisasi ini turut memperkuat kecenderungan individualistis milenial, mengisolasi diri mereka dari kontak langsung di dunia nyata. Perubahan sistem ekonomi ke arah digital ini juga menjadi ancaman baru bagi keberlanjutan praktik-praktik ekonomi konvensional yang ada, terutama sistem pasar tradisional dengan tingkat interaksi dan partisipasi sosial sangat tinggi antar pengunanya. Melalui proyek ini, peneliti berusaha menawarkan bentuk tipologi baru pasar tradisonal yang mendukung kedekatan sosial antar penggunanya terjalin intens, serta mempertahankan esensi pasar tradisional sebagai pusat sosial masyarakat. Rancang tipologi arsitektur yang ditawarkan oleh peneliti juga diharapkan memberi peluang seluas-luasnya bagi para penggunanya, teristimewa generasi milenial, untuk mengekplorasi berbagai peran sosial mereka dalam kegiatan ekonomi saat ini.